The Supramolecular Chemistry of Amphiphilic Redox-Active Organic-Inorganic Hybrid Polyoxometalates - Amin, Sharad (2021)
This thesis focuses on the synthesis and supramolecular assembly of Class II hybrid-POM amphiphiles, in which these molecules will be synthesized, characterized and their supramolecular assembly studied.